Signal Peptide Peptidase‐Like 2c (SPPL2c) impairs vesicular transport and cleavage of SNARE proteins. (7th February 2019) - Papadopoulou, Alkmini A; Müller, Stephan A; Mentrup, Torben; Shmueli, Merav D; Niemeyer, Johannes; Haug‐Kröper, Martina; von Blume, Julia; Mayerhofer, Artur; Feederle, Regina; Schröder, Bernd; Lichtenthaler, Stefan F; Fluhrer, Regina
Abstract: Members of the GxGD‐type intramembrane aspartyl proteases have emerged as key players not only in fundamental cellular processes such as B‐cell development or protein glycosylation, but also in development of pathologies, such as Alzheimer's disease or hepatitis virus infections. However, one member of this protease family, signal peptide peptidase‐like 2c (SPPL2c), remains orphan and its capability of proteolysis as well as its physiological function is still enigmatic. Here, we demonstrate that SPPL2c is catalytically active and identify a variety of SPPL2c candidate substrates using proteomics. The majority of the SPPL2c candidate substrates cluster to the biological process of vesicular trafficking. Analysis of selected SNARE proteins reveals proteolytic processing by SPPL2c that impairs vesicular transport and causes retention of cargo proteins in the endoplasmic reticulum. As a consequence, the integrity of subcellular compartments, in particular the Golgi, is disturbed. Together with a strikingly high physiological SPPL2c expression in testis, our data suggest involvement of SPPL2c in acrosome formation during spermatogenesis. Synopsis: Signal peptide peptidase‐like 2c (SPPL2c), thus far considered an orphan protease, is catalytically active and expressed in maturating spermatids. SPPL2c cleaves SNARE proteins and impairs vesicular transport and Golgi integrity. Proteomic analysis of HEK293 cells ectopically expressing SPPL2c reveals potential candidate substrates, among them various SNARE proteins. SPPL2c is a catalytically active intramembrane aspartyl protease of the GxGD‐type. SPPL2c supports acrosome formation in the maturating spermatids. Abstract : Signal peptide peptidase‐like 2c (SPPL2c), thus far considered an orphan protease, is catalytically active and expressed in maturating spermatids. SPPL2c cleaves SNARE proteins and impairs vesicular transport and Golgi integrity.